PERAN ARTIFICIAL INTELLIGENCE DALAM OTOMATISASI PROSES BISNIS DIGITAL: PELUANG DAN TANTANGAN - Adinda Jasmine Putri Nurazizah; Isnu Ardi; Julio Caesar Zambas (PT. ABIG RIZKY PUBLISHER, 2025)
This study aims to explore the role of Artificial Intelligence (AI) in the automation of digital business processes and to identify its benefits, challenges, and opportunities. The method used is a literature review by examining various scholarly sources such as journals, books, and research reports related to AI, digital transformation, and business process management. The findings indicate that AI plays a crucial role in enhancing operational efficiency, reducing errors, accelerating workflows, and driving service innovation. AI also supports data-driven decision-making and provides competitive advantages for organizations. However, the implementation of this technology faces several obstacles, including limited infrastructure, the need for technical expertise, high investment costs, as well as ethical and data security issues. Therefore, an integrated strategy and multi-stakeholder support are required to optimize the sustainable use of AI in digital business processes